Journey - MacLachlan, Patricia (New York : Bantam Doubleday Dell Books for Young Readers, 1993)
Left by their mother with their grandparents, two children feel as if their past has been erased until Grandfather finds a way to restore it to them.
"A Yearling book."
4.8
3-6
3-6
Wilson's Children
Wilson's Junior High School
Keywords: Mother and child -- Fiction; Grandparents -- Fiction; Mother-child relationship -- Fiction; Grandparents -- Fiction